Ag surface plasmon enhanced double-layer antireflection coatings for GaAs solar cells - 王彦硕 陈诺夫 张兴旺 杨晓丽 白一鸣 崔敏 汪宇 陈晓锋 黄添懋 (Journal of semiconductors, 2009)
Surface plasmon enhanced antireflection coatings for GaAs solar cells have been designed theoretically.The reflectance of double-layer antireflection coatings（ARCs） with different suspensions of Ag particles is calcu-lated as a function of the wavelength according to the optical interference matrix and the Mie theory.The mean dielectric concept was adopted in the simulations.A significant reduction of reflectance in the spectral region from 300 to 400 nm was found to be beneficial for the design of ARCs.A new SiO2/Ag-ZnS double-layer coating with better antireflection ability can be achieved if the particle volume fraction in ZnS is 1%-2%.